Results and Complications of Photorefractive Keratectomy - Khalid Masood Ashraf, Aneeq Ullah Baig Mirza (Pakistan Journal of Ophthalmology, 2006)
Purpose: To evaluate the results and identify the complications after photorefractive keratectomy (PRK). Materials and Methods: This retrospective study was conducted at Laser Vision Center, Model Town, Lahore. It comprised of 200 patients(400 eyes) that underwent PRK on Summit Apex Plus excimer laser from 20th Feb 2004 to 3rd June 2005. All consecutive patients with complete relevant data were included in the study. Three months postoperatively, the uncorrected visual acuity and complications in each eye, were recorded. The overall result was designed, based upon the postlaser uncorrected vision, residual refractive error, quality of vision and complications. Results: Out of 400 eyes, 383(95.9%) had a best corrected visual acuity of 6/9 or better preoperatively. At three months postoperatively, 369 eyes (92.3%) had an uncorrected vision of 6/9 or better. 51 eyes (12.8%) lost 2 or more lines of uncorrected visual acuity postoperatively. The main complications affecting the quality of vision postoperatively were under correction in 33 eyes (8.3%), poor contrast, shades, haloes and glare in 15 eyes (3.8%) and dry eye symptoms in 34 eyes (8.5%). The overall result was excellent in 311 eyes (77.8%). Conclusion: We believe that PRK is a reasonably safe and effective procedure for the correction of low to moderate myopia.